2014
DOI: 10.1136/bmjopen-2014-005026
|View full text |Cite
|
Sign up to set email alerts
|

What keeps family physicians busy in Portugal? A multicentre observational study of work other than direct patient contacts

Abstract: ObjectivesTo quantify the time spent by family physicians (FP) on tasks other than direct patient contact, to evaluate job satisfaction, to analyse the association between time spent on tasks and physician characteristics, the association between the number of tasks performed and physician characteristics and the association between time spent on tasks and job satisfaction.DesignCross-sectional, using time-and-motion techniques. Two workdays were documented by direct observation. A significance level of 0.05 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
3
18
1
9
Order By: Relevance
“…Physicians' generalized concerns on the impact of computer use could also be explained by the recent introduction of information system on Portuguese primary care units and by the fact that organizational and professional assignment are still ongoing [41]. One study, by Granja and collaborators, that evaluated tasks other than personal contact with patients by Portuguese family physicians, revealed that physicians spent, on average, 5.7 minutes daily with computer system malfunctions [51]. It is natural that positive expectations about information system become defrauded and physicians feel overloaded by the time spent with disturbing computer errors and troubles related to its malfunction.…”
Section: The Impact Of Computer Use In Clinical Communicationmentioning
confidence: 99%
“…Physicians' generalized concerns on the impact of computer use could also be explained by the recent introduction of information system on Portuguese primary care units and by the fact that organizational and professional assignment are still ongoing [41]. One study, by Granja and collaborators, that evaluated tasks other than personal contact with patients by Portuguese family physicians, revealed that physicians spent, on average, 5.7 minutes daily with computer system malfunctions [51]. It is natural that positive expectations about information system become defrauded and physicians feel overloaded by the time spent with disturbing computer errors and troubles related to its malfunction.…”
Section: The Impact Of Computer Use In Clinical Communicationmentioning
confidence: 99%
“…Nas USF-A, esta situação poderá ter menos importância porque o efeito do P4P é atenuado pelo facto de os incentivos serem pagos à equipa e não aos profissionais. Apesar de esta situação não ocorrer nas UCSP, o grande número de doentes que têm que tratar e o número insuficiente de médicos de família em algumas regiões [31] não são favoráveis à realização de consultas longas [32]. …”
Section: Cuidados De Saúde Primáriosunclassified
“…A multicentre observational study of work other than direct patient contacts teve, entre outros objetivos, o de quantificar o tempo consumido, pelos Médicos de Família Portugueses, noutras tarefas que não o contacto direto com o paciente. 12 Neste estudo de Granja et al, o tempo médio gasto noutras tarefas, que não o contacto direto com o paciente, foi superior a 11 horas semanais, valor inferior ao de outros estudos realizados nos EUA. 12 Metade do tempo gasto nestas tarefas, sem contacto direto com o paciente, esteve diretamente relacionado com atividade assistencial, permitindo garantir a acessibilidade, a continuidade e a coordenação de cuidados.…”
unclassified
“…12 Neste estudo de Granja et al, o tempo médio gasto noutras tarefas, que não o contacto direto com o paciente, foi superior a 11 horas semanais, valor inferior ao de outros estudos realizados nos EUA. 12 Metade do tempo gasto nestas tarefas, sem contacto direto com o paciente, esteve diretamente relacionado com atividade assistencial, permitindo garantir a acessibilidade, a continuidade e a coordenação de cuidados. 12 Olhando para a realidade Portuguesa, existe um paradoxo preocupante entre a necessidade de tempo protegido para tarefas que trazem melhoria de eficiência assistencial, bem como possibilidade de reflexão sobre a prática e investigação e a prioridade dada à atividade assistencial direta, com restrição temporal (quantidade vs qualidade) definida pelos decisores.…”
unclassified
See 1 more Smart Citation